2018
DOI: 10.4269/ajtmh.18-0157
|View full text |Cite
|
Sign up to set email alerts
|

Human Strongyloidiasis in Hawaii: A Retrospective Review of Enzyme-Linked Immunosorbent Assay Serodiagnostic Testing

Abstract: Human strongyloidiasis is widely prevalent in tropical and subtropical regions worldwide but is not endemic in Hawaii. Subclinical, chronic infections may be lifelong; immunosuppressive therapy, particularly with glucocorticoids, may lead to serious or fatal disseminated disease, which is preventable. We performed a retrospective analysis of patients tested for immunoglobulin G antibody in an academic medical center in Honolulu, Hawaii, from 2005 to 2012. Of the 475 patients tested, 78 (16%) were seropositive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Due to the unique autoinfection cycle exhibited by Strongyloides, lifelong latent infection can occur. Given increased global mobility, the CDC recommends that all individuals who have ever resided in S. stercoralis-endemic areas should be screened for asymptomatic S. stercoralis infection prior to administration of steroids [8], immunosuppressive agents, or chemotherapy [1]. Also, the test has the potential for commercial translation, up-scaling and making an impact on disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unique autoinfection cycle exhibited by Strongyloides, lifelong latent infection can occur. Given increased global mobility, the CDC recommends that all individuals who have ever resided in S. stercoralis-endemic areas should be screened for asymptomatic S. stercoralis infection prior to administration of steroids [8], immunosuppressive agents, or chemotherapy [1]. Also, the test has the potential for commercial translation, up-scaling and making an impact on disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Outside Latin America, in Southeast Asia and the Pacific, Akiyama and Brown reported a seroprevalence of 16% in 475 residents of Hawaii; the largest proportion of seropositive cases was found in Micronesians (30%) [34]. In Vietnam, Diep et al [35] observed a sero-reactivity to S. stercoralis in 29.1% of adults (N = 1340) and 5.5% of children (N = 270); men were more frequently sero-reactive when living in rural central highlands.…”
Section: Discussionmentioning
confidence: 99%